Вiк кори вивiтрювання пiвнiчно-захiдної частини Українського щита - Михайлов, В.А.; Приходько, В.К. (Видавничий дім "Академперіодика" НАН України, 2008)
The genesis of the platform stage of the Ukrainian Shield’s weathering crust is considered. There are three horizons of the weathering crust: Neoproterozoic, Carbonaceous, and Jurassic-Lower Cretaceous ones.